Environmental Factors that Influence the Geography of Yemen Leading to Dust and Sand Storms - A Case Study - Ghalib, Wadie Ahmed Mokbel; Mansoor, Almoliki Mohammed; Ponnappa, Sajan Chimmikuttanda (Journal of Environmental Geography, 2021)
In Yemen, the dust storm is a common phenomenon severely affecting the economy and health. Yemen is located in a semi-desert desert area, where dust and sand storms occur all year round, however they are the most common at summer (from June until the end of September). Coastal areas (Hajjah, Hoddeidah, Taiz, Lahg, Aden, Abyan, Shabwah and Hadramout) and desert areas (Marib and Al Jowf) are affected by dust and sandstorms almost all year round. The western and central governorates of Yemen are mountainous regions, but influenced by dust too. Dust storms in Yemen have an impact on humans, animals, plants and all environmental ecosystems. In this article, we attempted to understand the possible relationship between environmental parameters such as wind temperature, and precipitation, which influence the development of dust and sand storms in and around Yemen. Statistical analysis such as descriptive statistics, T-test, ANOVA one-way test, Tukey test, Levene test, and Correlation test were performed. The statistical analysis confirms that there is a significant correlation between wind, temperature and precipitation at 0.01 and 0.05 levels. The results further depict that environmental factors play a vital role in the formation of dust and sand storm. The results obtained are encouraging and further research will be conducted based on technological evidence.